2016
DOI: 10.1371/journal.pone.0156941
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Strong Ion Difference as a Marker of Renal Dysfunction. A Retrospective Analysis

Abstract: IntroductionThe kidneys play a crucial role in the regulation of electrolytes and acid-base homeostasis. Urinary Strong Ion Difference (SIDu = NaU + KU—ClU) represents an important aspect of renal acid-base regulation. We evaluated the role of SIDu as a marker of renal dysfunction in critically ill patients.Materials and MethodsPatients admitted to the Medical Intensive Care Unit with a diagnosis of AKI for whom concomitant urinary samples available for SIDu calculation were retrospectively reviewed and staged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…16,27,28 Balsorano et al demonstrated similar findings in their study, albeit not with the investigation of chloride excretion. 21 However, on direct measurement of urinary ammonium, we did not find a significant decrease in its concentration. The reason for this is unclear.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…16,27,28 Balsorano et al demonstrated similar findings in their study, albeit not with the investigation of chloride excretion. 21 However, on direct measurement of urinary ammonium, we did not find a significant decrease in its concentration. The reason for this is unclear.…”
Section: Discussioncontrasting
confidence: 56%
“…The urinary strong ion difference (SID, SID Urine ) was calculated from the collected data, using the following equation 21 :…”
Section: Data Collectionmentioning
confidence: 99%
“…Urinary strong ion difference ([SID] urine ) is used to differentiate renal hyperchloremic metabolic acidosis from non-renal causes (Balsorano et al 2016). Additionally, [SID] urine may help in our understanding of the mechanisms involved in paradoxical aciduria (Constable et al 2009).…”
Section: Introductionmentioning
confidence: 99%